Upaya Dosen Dalam Menumbuhkan Motivasi Karakter Mahasiswa Semester 4 Di Pembelajaran Jarak Jauh Pada Era Digital Di Universitas Terbuka - Jayani, Nanang; Azizah, Maratul (WASPADA (Jurnal Wawasan Pengembangan Pendidikan), 2025)
This study aims to describe or illustrate how to foster student character motivation in distance learning inthe digital era. Using a qualitative descriptive approach model carried out in this study using observation,interviews, documentation, and literature studies. The subjects in this study were 4th semester students at theOpen University. The conclusion of this study is to explain and describe the implementation of distancelearning in the digital era, so that in its development motivation and willingness are needed and so thatstudents have a character that motivates competence and is capable of digital literacy. And Komalasari,(2017 p. 83) formulated four guidelines in developing student character skills as follows: (1) there is a focusof attention given to life, in the sense of trying to direct people's attention to various aspects of their ownlives, so that they can identify the things they value; (2) there is acceptance that is in accordance with whatis, in the sense that when we pay attention to value clarification, we need to accept other people's positionswithout consideration, according to what is; (3) there is a stimulus to act further. Meaning, we need to domore as a reflection of values, rather than just accepting; (4) there is development of individual characterabilities. This means that with this approach, it is opened not only to develop students' skills in having valueclarification, but also to receive guidance to think and act further.Keywords: Cultivating character motivation, Distance learning, digital literacy